Redefinição do conceito de serviço de bibliotecas universitárias perante as mudanças tecnológicas - Bacalgini, Bruna [UNESP]; da Silva, Márcia Terra (My University, 2015)
Academic libraries pass through transformations with information and communication technologies (ICT), which also affect higher education and scientific communication. The literature shows that due to technological and external environment changes, the current concept of service of academic library does not attend new demands of its users. This article has as objective to present changes in the service concept of academic library through a systematic review of the literature in order to discuss that adaptation and the survival of library services depend on the conceptual redefinition of its service and the consequent operation of this.
Redefinition of the concept of service of academic libraries face to technological changes
Keywords: Academic library; Service concept; Service management